Ciência, senso comum e práticas de ensino de língua portuguesa - Andrade, Alexandra Karla Rodrigues (2018)
This dissertation investigates the relationship between Science, Common Sense and Portuguese language teaching practices for teachers. For this, we seek to evidence the concepts of Science, Common Sense and practices in the Theory of Social Representations, proposed by Moscovici among other scholars. Such support made it possible to understand that scientific knowledge is indispensable for the teaching and learning process of teachers, but they do not structure themselves. In teaching practice, as well as in TRS, common sense plays an important role, since it is necessary to value the experience and the practical way of practicing these professionals. We are researching a group of professionals who know and dominate the theme: teaching. The way they appropriate scientific knowledge and relate to their practical experience leads us to have a group that associates different theoretical fields in favor of the teaching and learning of its students, often joining theoretical contributions with different lines of research. For this, the field research has two groups of Portuguese Language teachers of the state public network: the first exploratory and constructed through the focal group and the second systematized. We think of three categories of analysis: teaching, how to teach and learning the Portuguese language. We tried to verify the similarities and the differences of the voices between the components of the groups. Finally, we cross the similarities of thought between the two groups in order to give teachers a voice about the practice of teaching.